Yield curve dynamics and fiscal policy shocks - Adam Kučera; Evžen Kočenda; Aleš Maršál (Charles University in Prague, Institute of Economic Studies (IES), 2022)
We show that government spending does play a role in shaping the yield curve which has important consequences for the cost of private and government financing. We combine government spending shock identification strategies from the fiscal macro literature with recent advancements in no-arbitrage affine term structure modeling, where we account for time-varying macroeconomic trends in inflation and the equilibrium real interest rate. We stress in our empirical macro-finance framework the importance of timing in the response of yields to government spending. We find that the yield curve responds positively but mildly to a surprise in government spending shocks where the rise in risk-neutral yields is compensated by a drop in nominal term premia. The news shock in expectations about future expenditures decreases yields across all maturities. Complementarily, we also analyze the effect of fiscal policy uncertainty where higher fiscal uncertainty lowers yields.
Keywords: C38; C51; C58; E43; E47; 330; Government Expenditures; Fiscal policy; U.S. Treasury Yield Curve; Affine Term Structure Model